Pengaruh ECU (Electronic Control Unit) dan Variasi tipe Jumlah Hole Injector Terhadap Performa Engine Single Cylinder 4 Langkah - Aureo Adriyanto Da Costa Amaral; Naili Saidatin; Rizal Mahmud; Iis Rohmawati (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
Study of Engine performance of vehicles was to be a complicated due to some influencing factors on it. Firstly, the entering stage of air-fuel into the combustion chamber, the combustion process, and thus after combustion to the exhaust stage. An important thing on the injection fuel system is ECU (Engine Control Unit) related to the function of the divided current controller; it is obtained to engine part. It part control lines from the fuel pump to injector. This study uses ECU variation (standard and Juken 5 racing turbo). The number of hole injector is commonly 6 and 8 and be investigated to the engine performance. In this case, dynamometer chassis were used to measure torque and engine power. The type of engine performed a 4 strokes-single-cylinder and powered by a fuel injection. The result shows the using ECU racing of the 8-hole injector has a significant effect on the engine performance; its performance appeared at engine power. These phenomena were also exhibited coincide single cylinder 4 strokes. Keywords: engine performance, ECU racing, and hole injector.